Interferon-induced transmembrane proteins inhibit cell fusion mediated by trophoblast syncytins - Zani, Ashley (J Biol Chem, 2019)
Type I interferon (IFN) induced by virus infections during pregnancy can cause placental damage, but the mechanisms and identities of IFN-stimulated genes that are involved in this damage remain under investigation. The IFN-induced transmembrane proteins (IFITMs) inhibit virus infections by preventing virus membrane fusion with cells and by inhibiting fusion of infected cells (syncytialization). Fusion of placental trophoblasts via expression of endogenous retroviral fusogens known as syncytins forms the syncytiotrophoblast, a multinucleated cell structure essential for fetal development. We found here that IFN blocks fusion of BeWo human placental trophoblasts. Stably expressed IFITM1, -2, and -3 also blocked fusion of these trophoblasts while making them more resistant to virus infections. Conversely, stable IFITM knockdowns in BeWo trophoblasts increased their spontaneous fusion and allowed fusion in the presence of IFN while also making the cells more susceptible to virus infection. We additionally found that exogenous expression of IFITMs in HEK293T cells blocked fusion with cells expressing syncytin-1 or syncytin-2, confirming the ability of IFITMs to block individual syncytin-mediated fusion. Overall, our data indicate that IFITMs inhibit trophoblast fusion and suggest that there may be a critical balance between these antifusogenic effects and the beneficial antiviral effects of IFITMs in virus infections during pregnancy.